An Analysis Of Teachers’ Strategies In Teaching Speaking Skills To High School Students - Lisa Kira Putri; Nuzulul Isna; Puan Tursina (Journal Informatic, Education and Management (JIEM), 2025)
This study aims to identify strategies employed by English teachers to enhance high school students’ speaking skills and to explore the challenges encountered in speaking instruction. A descriptive qualitative design was applied, with data collected through semi-structured interviews involving nine teachers from three sub-districts in Southwest Aceh. Data analysis followed Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing with verification. The findings reveal that the strategies used include direct practice, role play, grammar translation, group discussion, interviews, cooperative learning, listen-and-repeat, video dialogue, and filler activities such as singing, games, icebreakers, and warm-ups. The most frequently implemented strategy was direct practice, proven effective in improving students’ fluency, accuracy, and confidence. However, teachers faced challenges such as limited study time at home, low motivation, lack of vocabulary, inattentiveness, and low self-confidence. The study recommends integrating interactive strategies with educational technology and fostering a supportive learning environment to encourage students to speak confidently and stay motivated.